Networked supervisory control with imperfect communication channels - Zhu, Yuting (Nanyang Technological University, 2022)
This Ph.D. thesis addresses the challenging problem of networked supervisory control for (timed) discrete event systems against delays and losses in the communication channels, with an emphasis on a reinterpretation of the feedback closed-loop system that allows one to bring the networked synthesis problem much closer to the Ramadge-Wonham supervisory control problem, the latter of which is fundamentally rooted in a non-networked setting. This non-classical viewpoint presented in this work allows one to use the many techniques and tools that have been developed over the years to solve the networked supervisory control problem. Indeed, the main aim of this work is to show that the networked supervisory control problem is reducible to the non-networked supervisory control problem, with an exponential blowup in the state sizes due to the necessity of modelling the channels' behaviors. Before we present our main results, the state-of-art research works on networked supervisory control of discrete-event systems addressing the channel imperfections are discussed. By presenting the key concepts and main results of each representative work, we analyze the pros and cons of different approaches. We also provide a summary of the existing works, which roughly follow two different lines of thinking and result in two different verification or synthesis approaches. The first approach utilizes non-networked plant models but relies on the development of sophisticated concepts of network controllability and observability to capture the network imperfections, while the second approach embeds relatively complex yet verifiable channel models into the model of the networked plant and adopts the standard concepts of controllability and observability for the (verification and) synthesis of networked supervisors.